Advices for Preventing COVID-19 in Construction Workers’ Camp, in The Army Area - Kannirun, Metha (Journal of The Royal Thai Army Nurses, 2022)
In Thailand, there are many people make a living by being construction worker. The workers tend to live in crowded group, result in higher risk of spreading of COVID-19. From the “Measure to prevent the spread of COVID-19” published either by Department of Health, Ministry of Public Health, or by Division of Health Promotion and Preventive Medicine, Royal Thai Army Medical Department, still missing in some parts that could be fulfilled to accommodate the situation as it alters periodically. The army should choose “COVID-19 preventive measure in workers’ camp” proposed from this study, and conduct simultaneously in all levels (policy, personal, environment) in order to create a better workers’ camp. And there should be update for latest information periodically as the newer guideline comes out in the future.